The Associated Factors in the Prevalence of Motorcycle Accidents - Rahim Khan, Abbas Ali, Kamran Saeed, Muhammad Adnan Sadiq, Aizaz Ali Shah, Adeela Amber (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study was to examine the types of fractures sustained and damage patterns among bike trauma patients who were sent to the emergency department. Study design: Retrospective study Place and duration of study: Department of Orthopedic, Khyber Teaching Hospital Peshawar, From September, 2021 to February, 2022. Methods: In this study, 170 patients of motorcycle accidents were taken to investigate the factors associated with the accidents. The collected data included the demographic variables, fractures experienced, patterns of injury, time of accident, types of accident and the possible causes of accidents. Detailed demographics of enrolled cases included age, sex, BMI and localities were recorded after taking informed written consent. Data analysis was performed in SPSS-21.0. Results : A total of 170 patients of motorcycle accidents were conducted to study in which 119 (70%) were males and the rest 51 (30%) were females. The mean age of the patients was 29.6 years. The most common type of accident was car-bike collision that of 65.1%. Most of the deaths were occurred due to the head injury that accounted for 51.1%. The significant association of age, sex, ignorance of safety measures and types of roads with motorcycle accidents was shown in the multiple logistic regression analysis. Conclusion: Motorcycle accidents caused severe life threatening injuries to the patients. Rate of mortality was high among the patients with head injury. Males were more affected by the accidents as they were more in numbers. Accidents were more occurred in the population with age category of 18-27 years. Therefore, significant safety measures can reduce the risks of motorcycle accidents. Keywords: multiple injuries, motorcycle accidents, mortality.